2020
DOI: 10.1093/jpe/rtaa016
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank dynamics of an invasive alien species, Helianthus annuus L.

Abstract: Aims The ability to form persistent seed banks is one of the best predictors of species’ potential to establish in new ranges. Wild sunflower is native to North America where the formation of persistent seed banks is promoted by disturbance and it plays a key role on the establishment and persistence of native populations. However, the role of the seed banks on the establishment and persistence of invasive populations has not been studied. Here, we evaluated the role of seed bank and disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…In contrast, in a recent seed bank study, no differences in the timing of emergence were observed between the high dormant BAR and the low dormant CROP and DIA, all biotypes showed similar emergence timing during late winter (Presotto et al . 2020). Such differences may be attributable to the environmental conditions that seeds experienced after dispersal in the different experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in a recent seed bank study, no differences in the timing of emergence were observed between the high dormant BAR and the low dormant CROP and DIA, all biotypes showed similar emergence timing during late winter (Presotto et al . 2020). Such differences may be attributable to the environmental conditions that seeds experienced after dispersal in the different experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the soil seed bank, seed persistence is influenced by seed characteristics (seed size, dormancy, longevity), by local climate (temperature, humidity) and by external factors such as human disturbance with agricultural machinery (Presotto et al . 2020). Finally, a successful establishment of overwinter survivals will depend on seedlings´ tolerance to intraspecific and interspecific competence (Mercer et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive species usually germinate from persistent seed banks after disturbances that alter environmental conditions such as light and temperature ( Presotto et al 2020 ). Seeds can be resistant to environmental stresses (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among these traits, seed dormancy and herbicide resistance are among the most important for the successful establishment of weeds. Seed dormancy plays a crucial ecological role, contributing to avoidance of out of season germination (Presotto et al, 2020; Hernández et al, 2021), and persistence in soil seed banks (Darmency et al, 2017; Pipatpongpinyo et al, 2020; Presotto et al, 2020). On the other hand, the high killing rates associated with herbicide applications exert strong selection pressure for herbicide resistance (Darmency et al, 2017; Kreiner et al, 2018; Tranel and Wright, 2002).…”
Section: Introductionmentioning
confidence: 99%